Dynamic Inconsistency in Food Choice: Experimental Evidence from Two Food Deserts. (20th May 2019) - Sadoff, Sally; Samek, Anya; Sprenger, Charles
Abstract: We conduct field experiments to investigate dynamic inconsistency and commitment demand in food choice. In two home grocery delivery programs, we document substantial dynamic inconsistency between advance and immediate choices. When given the option to commit to their advance choices, around half of subjects take it up. Commitment demand is negatively correlated with dynamic inconsistency, suggesting those with larger self-control problems are less likely to be aware thereof. We evaluate the welfare consequences of dynamic inconsistency and commitment policies with utility measures based on advance, immediate, and unambiguous choices. Simply offering commitment has limited welfare (and behavioural) consequences under all measures.